Quantitative Blood Velocity Mapping in Glomerular Capillaries by in vivo Observation with an Intravital Videomicroscope - Ogasawara, Y.; Takehara, K.; Yamamoto, T.; Hashimoto, R.; Nakamoto, H.; Kajiya, F. (Methods of Information in Medicine, 2000)
We have evaluated rat glomerular microcirculation under in-vivo condition with an intravital videomicroscope. To measure erythrocyte velocities, a line segment was set along the glomerular capillaries in time-sequential videotaped images and then a spatiotemporal image was constructed along that segment. The angle of striped pattern in the spatio-temporal image which reflects the erythrocyte velocity, was estimated to compute erythrocyte velocity vector mapping. We found that erythrocyte velocities in rat glomeruli were significantly faster in diabetic rats than in control rats (p <0.05). In conclusion, we have succeeded in quantitatively evaluating the in-vivo renal microcirculation with our videomicroscope system and by spatiotemporal image analyzing method.
Keywords: Erythrocyte Velocity; Glomerulus; Renal Microcirculation; Spatiotemporal Image; Velocity Mapping